A comparison of burn related injuries following the natural disaster Super Storm Hurricane Sandy to the National Burn Repository of the American Burn Association. Issue 1 (December 2016) - Kalina, Michael; Malyutin, Grigoriy; Cooper, Michael
Abstract Background Burn related injuries from natural disasters are not well described and natural disasters are not identified as an etiology of burn injury in the National Burn Repository (NBR) of the American Burn Association. The natural disaster Super Storm Hurricane Sandy had devastating effects. Our goal was to detail the burn related injuries following this natural disaster and to compare the data to the NBR. Methods This was a retrospective chart review of thirty four patients who sustained burn related injuries following Super Storm Hurricane Sandy (SSHS) and were managed at Staten Island University Hospital Burn Center. Institutional Review Board approval was obtained. Data variables included age, gender, race, past medical history (PMHx), burn type, percentage total body surface area (%TBSA), hospital length of stay (HLOS), and mortality. We compared data from SSHS to the 2003-2013 NBR. Categorical data were summarized using frequency counts, percentages and Clopper-Pearson 95 % confidence interval for proportion. Continuous outcome data were summarized by descriptive statistics. Data analyses performed with SAS® System Version 9.3 (SAS Institute Inc., Cary, NC) andp  < 0.05 was significant. Results In the SSHS group, average age was 36 + 24 years, range 1-80 years, and 44.1 % were males (15/34, 95 % CI: 27.2 - 62.1). Caucasians comprised 58.8 %, (20/34, 95 % CI: 40.7, 75.4) and 73.5 % had no PMHx (25/34, 95 % CI: 55.6, 87.1). The most common burn type was scald, 55.9 %, (19/34, 95 % CI: 37.9, 72.8) and %TBSA ranged 1 %–47 %, average of 7 % + 12 %. The average HLOS was 13 + 26 days, range of 1–113 days. Mortality was 2.9 % (1/34, 95 % CI: 0.07–15). In comparison, the NBR reported an average age of 32 years and 69 % were males. Caucasians comprised 59.1 %. The most common burn type was flame, 43.2 % and the %TBSA ranged 1 %–9.9 %. HLOS ranged 8.4–10.2 days and mortality was 3.4 %. Conclusion We conclude that burn related injuries following a natural disaster differ as compared to those most commonly reported in the NBR.